Frey's syndrome: A misdirected reflex action!! - A case report - Anuradha Ganesan; Bounika E Rao (Wolters Kluwer Medknow Publications, 2021)
The incidence of Frey's syndrome after parotidectomy greatly varies in the literature. It is a sequelae of any surgery near the pretragal region like parotidectomy or condylar surgeries which might cause embarrassment and considerable social discomfort and may further result in disruptions and disturbances in daily life. Hence, frequent follow-ups after the surgeries, early diagnosis, and proper management of Frey's syndrome may help to alleviate symptoms and improve quality of life for the patient. This case report highlights a case of Frey's syndrome followed by the surgical management of condylar fracture and also highlights the management of the syndrome.